Semi-Automated Quantification of Retinal and Choroidal Biomarkers in Retinal Vascular Diseases: Agreement of Spectral-Domain Optical Coherence Tomography with and without Enhanced Depth Imaging Mode - Lucy J. Kessler; Dmitrii Bagautdinov; Grzegorz Łabuz; Gerd U. Auffarth; Ramin Khoramnia (Diagnostics, 2022)
Background: We compared with and without enhanced depth imaging mode (EDI) in semi-automated quantification of retinal and choroidal biomarkers in optical coherence tomography (OCT) in patients with diabetic retinopathy (DR) or retinal vein occlusion (RVO) complicated by macular edema. We chose to study three OCT biomarkers: the numbers of hyperreflective foci (HF), the ellipsoid zone reflectivity ratio (EZR) and the choroidal vascularity index (CVI), all known to be correlated with visual acuity changes or treatment outcomes. Methods: In a single examination, one eye of each patient (n = 60; diabetic retinopathy: n = 27, retinal vein occlusion: n = 33) underwent macular 870 nm spectral domain-OCT (SD-OCT) B-scans without and with EDI mode. Semi-automated quantification of HF, EZR and CVI was applied according to preexisting published protocols. Paired Student’s t-test or Wilcoxon rank-sum test was used to test for differences in subgroups. Intraclass correlation coefficient (ICC) and Bland–Altman plots were applied to describe the agreement between quantification in EDI and conventional OCT mode. The effect of macular edema on semi-automated quantification was evaluated. Results: For the entire cohort, quantification of all three biomarkers was not significantly different in SD-OCT scans with and without EDI mode (p > 0.05). ICC was 0.78, 0.90 and 0.80 for HF, EZR and CVI. The presence of macular edema led to significant differences in the quantification of hyperreflective foci (without EDI: 80.00 ± 33.70, with EDI: 92.08 ± 38.11; mean difference: 12.09, p = 0.03), but not in the quantification of EZR and CVI (p > 0.05). Conclusion: Quantification of EZR and CVI was comparable whether or not EDI mode was used. In conclusion, both retinal and choroidal biomarkers can be quantified from one single 870 nm SD-OCT EDI image.